The performativity of non-racialism and a culture of complaint - Hook, Derek (PINS-Psychology in Society, 2025)
Mashele, Prince (2011) The death of our society. Pretoria: CPR Press. ISBN 978-0-620-50196-5 pbk. Pages 153. Mashele’s shrill and often exasperating essay pinpoints a series of factors underlying the apparent decline – even the death – of South African society. This somewhat melodramatic tone is seemingly belied by the vibrancy of contemporary political culture in the country, even if this culture is itself often marked by the type of responsibility-aversion, ritualized complaint and factional mud-slinging that Mashele laments.